Urinary Markers of Oxidative Stress Are Associated With Albuminuria But Not GFR Decline - Schei, Jørgen; Fuskevåg, Ole-Martin; Stefansson, Vidar Tor Nyborg; Solbu, Marit Dahl; Jenssen, Trond Geir; Eriksen, Bjørn Odvar; Melsom, Toralf (Kidney International Reports, 2017)
Source at https://doi.org/10.1016/j.ekir.2017.11.020 . Introduction : Markers of oxidative stress increase with age and are prevalent with chronic kidney disease. However, the role of oxidative stress markers as predictors for kidney function decline in the general population is unclear. Methods : We investigated whether a baseline urinary excretion of oxidative DNA damage (8-oxo-7,8-dihydro-2′-deoxyguanosine [8-oxodG]) and oxidative RNA damage (8-oxo-7,8-dihydroguanosine [8-oxoGuo]) was associated with the age-related glomerular filtration rate (GFR) decline or incident low-grade albuminuria during a median of 5.6 years of follow-up. In the Renal Iohexol Clearance Survey in the Sixth Tromsø Study, we measured GFR using iohexol clearance in 1591 participants without renal disease, diabetes, or cardiovascular disease. Low-grade albuminuria was defined as an albumin-creatinine ratio >1.13 mg/mmol. Results : The mean (SD) annual GFR change was −0.84 (2.00) ml/min per 1.73 m2 per year. In linear mixed models, urinary 8-oxodG and 8-oxoGuo levels were not associated with the GFR change rate. In a multivariable adjusted logistic regression model, a baseline urinary 8-oxoGuo in the highest quartile was associated with an increased risk of low-grade albuminuria at follow-up (odds ratio: 2.64; 95% confidence interval: 1.50–4.65). When the highest quartile of urinary 8-oxoGuo was added to the baseline model, the area under the receiver operating characteristics curve for predicting low-grade albuminuria at follow-up improved from 0.67 to 0.71 (P = 0.002). Conclusion : Oxidative stress measured as urinary 8-oxoGuo excretion was independently associated with incident low-grade albuminuria, but neither 8-oxoGuo nor 8-oxodG predicted an accelerated age-related GFR decline in a cohort representative of the middle-aged general population during almost 6 years of follow-up.